Perceived challenges and opportunities for basic scientists transitioning to basic science educators in medical and health professions education - Lik-Wei Wong; Amanda Huee-Ping Wong; Derrick Wen Quan Lian; Shing Chuan Hooi (Discover Education)
Abstract Basic science educators play a significant role in medical and health professions curricula, particularly in the biomedical science components. Although the shift from basic scientists to educators seems promising, no study has yet explored the transition process from the perspective of basic scientists themselves, especially in the early stages of their transition. An anonymous survey with voluntary participation was administered to all basic scientists in National University of Singapore (NUS) Yong Loo Lin School of Medicine. The survey aimed to identify the perceived challenges faced by basic scientists transitioning to basic science educators in medical and health professions education. This study consisted of Likert scale questions, followed by one multiple-choice question and two open-ended questions. Twenty-one basic scientists either postdoctoral fellows or instructors, completed the study. The study found that gaps in clinical content and experience, along with teaching pedagogy and training were among the major concerns for basic scientists aspiring to be basic science educators. These challenges and shortcomings could potentially be addressed by providing them with clinical shadowing opportunities, education mentorship and teaching training. Since most respondents lacked teaching experience, the results might differ if the majority had been involved in teaching within medical and health professions education. Nonetheless, it is important to understand and acknowledge the challenges and concerns experienced by basic scientists and examine how they can navigate them in the process of their transition to teaching medical and health professions. This also provides opportunities for personal reflection and development so that basic science educators will be more prepared for greater challenges and the ever-changing demands of contemporary medical and health professions education.